Natural infection by Paramphistomoidea Stiles and Goldberger, 1910 trematodes in wild Marsh Deer (Blastocerus dichotomus Illiger, 1815) from Sérgio Mottas's hydroelectric power station flooding area. - do Nascimento, Cristiano G; do Nascimento, Adjair A; Mapeli, Elaine B; Tebaldi, José H; Duarte, José M B; Hoppe, Estevam G Lux (My University, 2006)
Studies on helminthfauna of marsh deer Blastocerus dichotomus Illiger, 1815 are rare, although helminthic diseases are an important cause of mortality in these animals. Fifteen male and female adult marsh deer from Sergio Motta's hydroelectric power station flooding area at Paraná River which died during the capture and quarantine procedures, between 1998 and 1999, were necropsied. Three trematodes species, Paramphistomum cervi, Balanorchis anastrofus and Zygocotyle lunatum, all belonging to superfamily Paramphistomoidea, were identified. The obtained trematodes were identified, counted and their respectives descriptors of infection were determined. All necropsied animals were infected by helminths. Paramphistomum cervi was the most prevalent species, while Zygocotyle lunatum was found in only one animal.
Keywords: animal; animal disease; Brazil; deer; histology; parasitology; trematode; trematodiasis; Animals; Deer; Paramphistomatidae; Trematode Infections